Prospects of introduction of international standards of financial reporting in Uzbekistan, issues of improving the system (Eurasian Research Bulletin, 2024)
In this article, the normative and legal bases of the organization of joint-stock companies, their role and importance in the economy are usually connected with their large-scale financial and economic activities. Proposals and recommendations have been made on the issues that should be introduced, with the main focus on improving management efficiency, increasing the capitalization of the company